Adherence to the 2018 WCRF/AICR cancer prevention guidelines and chronic lymphocytic leukemia in the MCC-Spain study. (February 2020) - Solans, Marta; Romaguera, Dora; Gracia-Lavedan, Esther; Molinuevo, Amaia; Benavente, Yolanda; Saez, Marc; Marcos-Gragera, Rafael; Costas, Laura; Robles, Claudia; Alonso, Esther; de la Banda, Esmeralda; Gonzalez-Barca, Eva; et al.
Highlights: The 2018 WCRF/AICR guidelines were examined in relation to chronic lymphocytic leukemia (CLL). 318 CLL cases and 1293 controls from the MCC-Spain study were included. Adherence to the 2018 WCRF/AICR recommendations was not associated with CLL. Abstract: Introduction: Preventable risk factors for chronic lymphocytic leukemia (CLL) remain largely unknown. The aim of this study was to evaluate the association between adherence to nutrition-based guidelines for cancer prevention and CLL, in the MCC-Spain case–control study. Methods: A total of 318 CLL cases and 1293 population-based controls were included in the present study. The World Cancer Research Fund/American Institute for Cancer Research (WCRC/AICR) score based on the 2018 recommendations for cancer prevention (on body fatness, physical activity, and diet) was constructed. We used logistic regression analysis adjusting for potential confounders. Results: Individuals in the highest tertile of the WCRF/AICR score had an odds ratio for CLL of 1.25 (95 % CI 0.91; 1.73) compared with individuals with low adherence (p-trend = 0.172). Each point increment in the score was associated with an OR for CLL of 1.06 (95 % CI 0.91; 1.23). Analyses by severity of disease did not show significant heterogeneity of effects. Conclusion: Overall, our results do not support an association between the WCRF/AICR score and CLL, yet we might have been limited by statistical power and study design to detect modest associations. Further research, ideally with a prospective design, long follow-up, and including additional lymphoma subtypes, is warranted to confirm the impact of composite healthy lifestyle behaviors on lymphoma risk.